Menjaga Kesehatan dalam Tatanan Hidup yang Sibuk Panduan Manajemen Kesehatan untuk Profesional Aktif - Moh arif Kusnadi; Dety Mulyanti (Universitas Muhamadiyah Manado, 2023)
Sport is one of a person's physical and psychological activities that is useful for maintaining and improving the quality of one's health after exercise. In office workers with very dense routines from morning to late, faced with deadlines, light mobilization, sitting too long, poorly trained muscles and wrong work positions will cause various complaints such as low back pain, neck complaints, shoulder complaints and not only limited to physical, but more susceptible to various diseases, such as coronary heart disease, high blood pressure, diabetes miletus, stroke etc. This research uses Literature Review research which is one method with collecting literature data, analyzing theories, structured evaluations, classifying and categorizing evidence-based that has existed or been produced before. The results of maintaining health in a busy life order must still be considered, by exercising and maintaining a lifestyle. To maintain motion is to sustain life, to increase the ability to move is to improve the quality of life.